(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article presents the results of scientific research on the effectiveness of using athletic gymnastics tools to strengthen students’ health, increase their physical performance, and improve their practical physical preparation for future professions. Certain recommendations are also provided in this regard.